The measures of self-regulated leaners in learning form four history - Lee, Yong May (Faculty of Education, UTM, 2012)
Intensive review of literature proposed that research on Self-regulated Learning (SRL) should be integrated into subjects in the classroom and thus, provides comprehensive picture and rich information for teachers and policy makers to design appropriate learning contexts for the Form Four students to learn History. The main purpose of this study is to investigate the motivation, learning strategies and achievement of Form Four students in learning History before and after the intervention program.